Stress distribution in endodontically treated external cervical resorption lesions restored with MTA and biodentine – A finite element analysis - Mudita Manaktala; Sonali Taneja; Vidhi Kiran Bhalla (Journal of Oral Biology and Craniofacial Research)
Introduction: Root resorption poses a significant challenge in dental practice, with external cervical resorption (ECR) being a common manifestation. ECR is often asymptomatic until advanced stages, complicating its diagnosis and management. Various factors contribute to its etiology, ranging from trauma to orthodontic treatment. The classification system proposed by Patel et al. (2018) offers a comprehensive framework for characterizing ECR lesions based on location and extent. Treatment strategies for ECR involve a combination of endodontic intervention and restorative techniques, with bioactive materials like mineral trioxide aggregate (MTA) and Biodentine emerging as promising options. However, the biomechanical behavior of teeth restored with these materials in the context of ECR remains underexplored. Materials and methods: This study utilized finite element analysis (FEA) to assess stress distribution in teeth with simulated ECR lesions of varying sizes and locations, restored with MTA or Biodentine. Three-dimensional models of maxillary central incisors were generated based on CBCT scans, incorporating periodontal ligament and surrounding bone structures. Eight experimental models representing different ECR configurations were created and subjected to FEA using Optistruct software based on dimensional classification given by Patel et al., in 2018, A70 M & A70B: 1Ap, A130 M & A130B: 1Bp, B70 M & B70B: 2Ap, B130 M & B130B: 2Bp. All the models were tested for stress distribution by restoring the lesions with either M: MTA or B: Biodentine. Oblique load of 100 N was applied at 45°angle to the long axis 2 mm lingual to incisal edge. vonMises Stress distribution in enamel, dentine, restoration and at all the interfaces were observed. Results: The analysis revealed that both MTA and Biodentine restorations exhibited uniform stress distribution around ECR lesions, with no significant differences based on lesion location or size. Maximum stress concentrations were observed around the restorations, particularly in subcrestal lesions. However, overall stress levels were comparable between MTA and Biodentine restorations, indicating similar biomechanical performance. Conclusion: Finite element analysis provides valuable insights into the biomechanical behavior of teeth with ECR lesions restored with MTA and Biodentine. Both materials exhibit similar stress distribution patterns and offer adequate reinforcement against mechanical forces. Clinicians can confidently utilize MTA or Biodentine in the management of ECR, considering their favorable biomechanical properties and clinical outcomes. Further research is necessary to validate these findings and optimize treatment protocols for ECR.